Factor that affecting employees attitude towards organization change in UMT / Nabihah Jasri - Jasri, Nabihah (Bachelor of Science (Hons) Statistics, 2015)
Universiti Malaysia Terengganu (UMT) is a relatively young university that was establish in year 2000 to increase access of higher education in Malaysia. Being young has helped UMT to transform itself into a mold not like any other universities in Malaysia. Transformation in structure of governance has been done in many universities throughout the world. With the strength from the effects of transformation, UMT will be able to achieve it vision to be a marine focused university that is reputed nationally and respected globally. The main objective of this study is to determine that there is a relationship between job stress, organizational commitment and organizational change. Before test the relationship, Kolmogorov-Smirnov, scatter plot and Q-Q plot were applied and the result showed normally distributed. Correlation had been chosen for analyzed. Job stress and organizational commitment has positive relationship between organizational changes. On further analysis using multiple linear regression, it was found that job stress and organizational commitment gave significant linear relationship on employees’ attitude towards organization change. This study may help the organization in UMT to improve their management and achieve their objective